Perancangan Prototype Sistem Pengelolaan Berkas berbasis Web pada Kantor Pelayanan Pajak Penanaman Modal Asing Dua Jakarta menggunakan Metode Human Centered Design - R. Arya Hasburrahman; Hanifah Muslimah Az-Zahra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
File management is very necessary for an institution, namely as the information center of a company. The existence of files or documents that are old will certainly make it difficult for companies to obtain data quickly and accurately. Based on the results of interviews with employees from the Foreign Investment Tax Service Office Dua, the appearance of the file management system in the office is not good and office staff also find it difficult to access the system. This implies that there are usability problems that arise because the system cannot be used by users to achieve their interests in accessing the system. The purpose of this study is to analyze the needs of users who are used in designing a web-based file management system at the Two Foreign Investment Tax Service Office, then design a solution from the File management information system at the Two Foreign Investment Tax Service Office, and evaluate the results of the system solution design. File management information at the Foreign Investment Tax Service Office Two. This study uses an interactive system development method, namely Human-Centered Design. The research stages start from planning the human centered design process, analyzing the context of use, analyzing user needs, evaluating the usability of the previous system, making a solution design, and evaluating the usability of the solution design. The results of this study are the usability value of the previous system was 43.25%, while the solution design increased to 77.25%, and the prototype of a web-based file management system at the Foreign Investment Tax Service Office Two Jakarta.